The Importance of Reactualizing Bung Hatta's Character in Islamic Religious Education at Universities - Muslim Muslim; Heri Effendi; Pebriyenni Pebriyenni; Siti Aisyah; Muspardi Muspardi (Institut Agama Islam Negeri Imam Bonjol Padang, 2024)
Reactualizing Bung Hatta's character in Islamic Religious Education (PAI) at universities is a strategic step towards shaping students who embody integrity, discipline, and responsibility. This is relevant in facing moral and ethical challenges in the modern era. This article aims to describe the importance of reactualizing Bung Hatta's character in PAI Learning at Higher Education Institutions. Data collection was conducted using in-depth interviews, participant observation, and documentary studies. The data were analyzed using Sugiyono's framework. This qualitative research employed a case study approach. The research object was the PGSD study program at the Faculty of Teacher Training and Education, Universitas Bung Hatta. The research subjects were PAI lecturers and all 2021 PGSD students. Data collection techniques included observation, interviews, and documentary studies. Data analysis followed Matthew B. Miles Huberman's model, encompassing data collection, data reduction, data presentation, and drawing conclusions. The research findings indicate the importance of reactualizing Bung Hatta's character in PAI Learning at the PGSD study program. Implementation strategies to integrate Bung Hatta's character in Islamic Religious Education include: 1) Developing a curriculum that aligns with contemporary values, 2) Interactive teaching methods, 3) Integration with modern contexts, and 4) Continuous assessment and feedback.